2012
DOI: 10.3748/wjg.v18.i32.4363
|View full text |Cite
|
Sign up to set email alerts
|

How many cases of laryngopharyngeal reflux suspected by laryngoscopy are gastroesophageal reflux disease-related?

Abstract: MII-pH analysis confirmed GERD diagnosis in less than 40% of patients with previous diagnosis of LPR, most likely because of the low specificity of the laryngoscopic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0
10

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 47 publications
2
107
0
10
Order By: Relevance
“…A classical find in case of reflux laryngopharyngitis is the persistence of barium in the valleculae and pyriform sinuses. This specific type of laryngopharyngitis shows a severe edema, hyperemia and phlogosis of posterior laryngeal wall and these signs, common but not exclusive of the LPR, are easily verifiable through a fiberoptic videolaryngoscopy (VLS) [24]. Symptoms such as vocal fatigue, hoarseness and globus pharyngeus, in a not yet well-defined percentages, if associated with edema and hyperemia of the arytenoid cartilage and interarytenoid area, salivary stagnation in the piriform sinus, vocal nodules, vocal fold edema determine the simple LPRD; if associated with granulomatous lesions of the posterior glottis, subglottic stenosis, precancerous lesions and carcinoma of the larynx, they determine the complicated LPRD [25].…”
Section: °Hypothesis: the Hyoid-laryngeal Elevation And Laryngopharymentioning
confidence: 99%
“…A classical find in case of reflux laryngopharyngitis is the persistence of barium in the valleculae and pyriform sinuses. This specific type of laryngopharyngitis shows a severe edema, hyperemia and phlogosis of posterior laryngeal wall and these signs, common but not exclusive of the LPR, are easily verifiable through a fiberoptic videolaryngoscopy (VLS) [24]. Symptoms such as vocal fatigue, hoarseness and globus pharyngeus, in a not yet well-defined percentages, if associated with edema and hyperemia of the arytenoid cartilage and interarytenoid area, salivary stagnation in the piriform sinus, vocal nodules, vocal fold edema determine the simple LPRD; if associated with granulomatous lesions of the posterior glottis, subglottic stenosis, precancerous lesions and carcinoma of the larynx, they determine the complicated LPRD [25].…”
Section: °Hypothesis: the Hyoid-laryngeal Elevation And Laryngopharymentioning
confidence: 99%
“…For instance, Lee et al 1 did not mention a study in IPF individuals performed with 24-hour impedance pH monitoring, which is nowadays considered to be the best test for measuring gastroesophageal reflux, also in case of atypical manifestations. [6][7][8] In this study, patients with IPF had significantly higher esophageal acid exposure and greater number of acid refluxes than controls, but also weakly acidic refluxes were remarkably increased. 9 Furthermore, more bile acids and pepsin were detected in both broncheoalveolar lavage fluid and saliva as strong confirmation of the risk of gastric aspiration in upper airways of these patients.…”
Section: To the Editormentioning
confidence: 80%
“…In our laboratory the detection of pepsin and bile acids in BAL of patients with GERD was also performed in a recent study 7 using impedance-pH monitoring, which is nowadays considered to be the best test for measuring gastroesophageal reflux, also in cases of atypical manifestations of GERD. [8][9][10] We found that patients with idiopathic pulmonary fibrosis had significantly higher esophageal acid exposure and greater number of acid refluxes than controls, but also that weakly acidic refluxes were remarkably increased. Moreover, more bile acids and pepsin were measured in BAL as a sound marker of gastric aspiration in the upper airways of these patients.…”
mentioning
confidence: 74%